Satisfaction of CM students with the socialized tuition system - Acedillo, Ma. Joanna B.; Arcan, Erika Althea B.; Aristoza, Ann Julienne A.; Daplas, Christel Angela D.; Graza, Niel Christian E. (University of the Philippines Visayas, College of Management, 2017)
The students of the University of the Philippines have been reacting negatively to its new financial assistance scheme, the Socialized Tuition System (STS) as issues of equitability, inaccuracy of results, and ineffectiveness of determining rightful brackets have been laid down. This all stems from the concepts of welfare and satisfaction - on how the administration perceives welfare, how the students receive this system, and whether there is coherence between both. In order to address this gap, the researchers have conducted a qualitative study on CM students in UP Visayas. This study aims to determine the efficiency, effectiveness, and accuracy of the STS, as well as the satisfaction Levels of CM students with it, and its relationship with variables like gender, year level, and current STS brackets. A sample of 156 students was drawn using Slovin's formula. As set in the objectives, the sample was classified according to gender (male, female), year level (batch XV, Nene, 13nium, and D12), and STS bracket (A, B, C, D, and E) to determine whether or not there is a direct relationship between the said variables and the CM students' knowledge about the STS and their corresponding satisfaction levels. After conducting the survey and gathering the results, it showed that CM students perceive the overall STS process as moderately efficient. It is to be noted, however, that they feel that the STS is not that effective in determining their brackets and that the bracketing results are mostly inaccurate. Specifically, it was found that gender is not determining factor in the satisfaction levels of the subjects towards the STS. With regard to year levels, the results showed no correlation between the two variables of age and STS awareness. Furthermore, no clear trend was also established between the brackets and their satisfaction levels, except for the fact that those under Bracket C gave the most extreme response (either extremely high or extremely low) for most of the questions. The neutral opinions of CM students show that even though they felt alleviation because of the shift to STS, the said system has still failed to provide them with an equitable and accurate basis of their tuition fees. Taking into account both inherent and explicit limitations, however, it is reommended that further studies about this be conducted.